2000
DOI: 10.1128/aem.66.5.2148-2153.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fluoropyrogallols as New Intermediates in Biotransformation of Monofluorophenols in Rhodococcus opacus 1cp

Abstract: Halophenols and their derivatives are priority pollutants of mainly anthropogenic origin. Over several decades, these compounds have been widely used as building blocks in chemical and pharmaceutical syntheses and as herbicides and pesticides, and they have caused serious local contamination of the environment. Soil microorganisms have developed the capacity of utilizing halophenols for their growth by a diverse set of biodegradation pathways (8). Aerobic soil microorganisms generally degrade mono-and dihaloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…strain FP1 (Duque et al 2012) as well as in Burkholderia fungorum strain FLU100 (Strunk and Engesser 2013). Moreover, further hydroxylated by-products like fluorohydroquinone or fluoropyrogallols may be formed (Finkelstein et al 2000;Kim et al 2010).…”
Section: Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…strain FP1 (Duque et al 2012) as well as in Burkholderia fungorum strain FLU100 (Strunk and Engesser 2013). Moreover, further hydroxylated by-products like fluorohydroquinone or fluoropyrogallols may be formed (Finkelstein et al 2000;Kim et al 2010).…”
Section: Phenolsmentioning
confidence: 99%
“…In Pseu do noc ardia benzenivorans, 2-fluorohydroquinone was detected as an additional product (Kim et al 2010), and in R. opacus 1cp, 4-fluorocatechol was hydroxylated to form 5-fluoropyrogallol (Finkelstein et al 2000). Tyrosinase from Streptomyces antibioticus, an enzyme known to catalyze the ortho-hydroxylation of monophenols and the subsequent oxidation of diphenols to quinones, converted 3-fluorophenol into 4-fluorinated 1,2-benzoquinone which then underwent nonenzymatic polymerization reactions, thereby releasing about 50 % of the fluorine contained.…”
Section: Phenolsmentioning
confidence: 99%
“…Aerobic biotransformation of 2-FP by several Rhodococcus strains (Bondar et al 1999;Finkelstein et al 2000), acclimated activated sludge (Chaojie et al 2007), Gloeophyllum striatum (Kramer et al 2004) and Penicillium strains (Hofrichter et al 1994;Marr et al 1996), has been reported. In all cases, 2-FP was degraded by cometabolism in the presence of other carbon sources.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, soil microorganisms have developed the capacity of utilizing halophenols for their growth by a diverse set of biodegradation pathways (Haggblom 1992). Furthermore, the microbial transformation of monofluorophenols by the whole cells of Rhodococcus opacus 1cp was investigated (Finkelstein et al 2000). However, up to now there are no reports concerning the biotransformation of monofluorophenols by cultured plant cells.…”
mentioning
confidence: 99%